Determination of Pharmacokinetic and Pharmacokinetic-Pharmacodynamic Parameters of Doxycycline against Edwardsiella ictaluri in Yellow Catfish (Pelteobagrus fulvidraco) - Ning Xu; Miao Li; Xiaohui Ai; Zhoumeng Lin (Antibiotics, 2021)
This study aimed to examine the pharmacokinetics of doxycycline (DC) in yellow catfish (Pelteobagrus fulvidraco) and to calculate related pharmacokinetic–pharmacodynamic (PK/PD) parameters of DC against Edwardsiella ictaluri. The minimum inhibitory concentration of DC against E. ictaluri was determined to be 500 µg/L. As the increase of oral dose from 10 to 40 mg/kg, the area under the concentration vs. time curve from 0 to 96 h (AUC0–96) values were considerably increased in gill, kidney, muscle and skin, and plasma, except in liver. Cmax values exhibited a similar dose-dependent increase trend in plasma and tissues except in liver, but other PK parameters had no apparent dose-dependence. The PK/PD parameter of the ratio of AUC0–96 to minimum inhibitory concentration (AUC0–96h/MIC) was markedly increased in plasma and tissues dose-dependently except in liver, but %T > MIC values were increased only moderately at some dose groups. After receiving the same dose with disparate time intervals from 96 to 12 h, the AUC0–96h/MIC was distinctly increased in plasma and tissues, but the %T > MIC had a decreasing trend. When administering 20 mg/kg with a time interval of 96 h, the AUC0–96h/MIC values were consistently >173.03 h and the %T > MIC values were above 99.47% in plasma and all tissues. These results suggest that administration of DC at 20 mg/kg every 96 h is a preferable regimen in yellow catfish.